6x=12-3x

Simple and best practice solution for 6x=12-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x=12-3x equation:


Simplifying
6x = 12 + -3x

Solving
6x = 12 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
6x + 3x = 12 + -3x + 3x

Combine like terms: 6x + 3x = 9x
9x = 12 + -3x + 3x

Combine like terms: -3x + 3x = 0
9x = 12 + 0
9x = 12

Divide each side by '9'.
x = 1.333333333

Simplifying
x = 1.333333333

See similar equations:

| 8x-4=4x-3 | | 5x-7+2*(3-5x)=-x+2 | | 127=4.4571*x+3 | | 7x+30x+4*(8x+1)=2*(22x+15)-1 | | 7x+30x+4*(8x+1)=2*(22x+15) | | 7x+30x+4*(8x+1)=2*(22x+15)+3 | | 7x+30x+4*(8x+1)=2*(22x+15)+1 | | 1+a=5 | | 5x+8+80=4x | | 3*(x-1)+7=x-5*(7-3x) | | 12x-10=134 | | 5x+2=50-3x | | 6=4k | | 5*(2x-6)=15 | | 10-x*x=4*x-8 | | -2x+3y=0 | | -2(-2x+6)= | | 8x+15=6x+11 | | 9-8x=69-43x | | 9-8x=69-43 | | 2(5-x)=4 | | 3=8-2d | | 5-4b=13 | | x^3-9x^2+18x-6=0 | | x^3+9x^2+18x-6=0 | | 5=6-2k | | 7x+4=3x-12 | | 8=18-5p | | 15-3t=0 | | 21-4m=5 | | 8n-3=3n+27 | | 137-6x=21x+20 |

Equations solver categories